Decoding Antisemitism: An AI-driven Study on Hate Speech and Imagery Online - Matthias J. Becker; Laura Ascone; Matthew Bolton; Veronika Bundzíková; Alexis Chapelan; Pia Haupeltshofer; Alexa Krugel; Iael Kurjan; Helena Mihaljević; Stefan Munnes; Karolina Placzynta; Milena Pustet; et al. (Technische Universität Berlin, Zentrum für Antisemitismusforschung, 2024)
The interdisciplinary research project "Decoding Antisemitism" aims to investigate antisemitism on the internet. Since summer 2020, this three-year pilot project has been based at the Centre for Research on Antisemitism (ZfA) at TU Berlin and is being carried out in cooperation with King's College London (KCL). The object of study is antisemitism in the comment sections of mainstream political media websites in Germany, France and the UK, as well as their social media profiles. Using a mixed methods approach, discursive trends in the three European countries and different verbal and visual forms of antisemitism are analysed qualitatively, quantitatively and with the help of AI. The interactive web presents itself as an object of study due to its central role in social discourse. By analysing the comments sections of media that belong to the politically moderate field, the research team is opening up a field that has received little attention so far - an urgent task, since the normalisation of derogatory and exclusionary rhetoric in such milieus poses an enormous danger. On the basis of extensive qualitative analyses, an overview of previously unknown manifestations and the actual extent of antisemitism in these European web communities will be gained. The results in turn offer the possibility of diverse counter-strategies. – – Das interdisziplinäre Forschungsprojekt ,,Decoding Antisemitism“ dient der Untersuchung von Antisemitismus im Internet. Seit Sommer 2020 ist dieses dreijährige Pilotprojekt am Zentrum für Antisemitismusforschung (ZfA) an der TU Berlin angesiedelt und wird in Zusammenarbeit mit der HTW Berlin und dem King's College London (KCL) durchgeführt. Beim Untersuchungsgegenstand handelt es sich um Antisemitismus in den Kommentarbereichen von Medien-Webseiten des politischen Mainstream in Deutschland, Frankreich und Großbritannien sowie deren Social Media-Profile. Über einen Mixed Methods-Zugang werden diskursive Trends in den drei europäischen Ländern und unterschiedliche verbale und visuelle Ausformungen von Antisemitismus qualitativ, quantitativ sowie KI-gestützt analysiert. Das Interaktive Web bietet sich aufgrund seiner zentralen Rolle im gesellschaftlichen Diskurs als Untersuchungsgegenstand an. Mit der Analyse von Kommentarbereichen jener Medien, die dem politisch gemäßigten Feld zuzurechnen sind, erschließt das Forscher*innenteam ein bislang wenig beachtetes Feld – zudem eine drängende Aufgabe, da von der Normalisierung abwertender und ausgrenzender Rhetorik in ebensolchen Milieus eine enorme Gefahr ausgeht. Auf der Basis umfangreicher qualitativer Analysen wird ein Überblick über bisher unbekannte Erscheinungsformen und das tatsächliche Ausmaß von Antisemitismus in diesen europäischen Web-Communitys gewonnen. Die Ergebnisse bieten wiederum die Möglichkeit vielfältiger Gegenstrategien.
Keywords: 300; antisemitism; anti-Semitism; pragmalinguistics; social media; hate speech; content analysis; Antisemitismus; Pragmalinguistic; Inhaltsanalyse; Hassrede